2004
DOI: 10.1097/00005537-200404000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Olfactory Dysfunction: The Skövde Population‐Based Study

Abstract: Objectives/Hypothesis Patients with olfactory dysfunction appear repeatedly in ear, nose, and throat practices, but the prevalence of such problems in the general adult population is not known. Therefore, the objectives were to investigate the prevalence of olfactory dysfunction in an adult Swedish population and to relate dysfunction to age, gender, diabetes mellitus, nasal polyps, and smoking habits. Study Design Cross‐sectional, population‐based epidemiological study. Methods A random sample of 1900 adult i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
435
4
20

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(501 citation statements)
references
References 30 publications
42
435
4
20
Order By: Relevance
“…Previous studies have further reported a relationship between olfactory dysfunction and diabetes [13][14][15][16][17][18], as well as an inverse relationship between olfactory identification and discrimination scores and the presence of diabetic complications [13,14,16,19,20]. Some authors have suggested that screening for olfactory dysfunction could serve as an early detector for the presence of diabetic microvascular complications, such as diabetic neuropathy [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have further reported a relationship between olfactory dysfunction and diabetes [13][14][15][16][17][18], as well as an inverse relationship between olfactory identification and discrimination scores and the presence of diabetic complications [13,14,16,19,20]. Some authors have suggested that screening for olfactory dysfunction could serve as an early detector for the presence of diabetic microvascular complications, such as diabetic neuropathy [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…The sensation of the smell of burnt or metallic smell in the absence of the stimulus is sometimes defined as 'torqosmia' [9]. In a large Swedish study, overall prevalence of hyposmia and anosmia in the general population were 13.3% and 5.8%, respectively [6], and similar proportions were reported in Germany [8]. One of the main factors related to olfactory dysfunction is aging [11], but several other causes are also known.…”
Section: Case Presentation and Discussionmentioning
confidence: 99%
“…The prevalence of subjects with the impairment of olfactory perception in the general population ranges from 1 up to 20% [6][7][8]. However, this is likely an underestimation, especially considering the fact that many people with a reduced olfactory sensitivity are unaware of their situation [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Similarly, 19% of Swedes were found to have hyposmia or anosmia. 25 Many times, the ability to smell diminishes gradually over time, making self-reported olfactory impairment substantially underestimated. 23 Patients frequently do not discuss their olfaction difficulties; however, the loss of smell can lead to depression and a lower quality of life.…”
Section: Discussionmentioning
confidence: 99%